Existence of Best Proximity Point with an Application to Nonlinear Integral Equations - Shagun Sharma; Sumit Chandok (Journal of Mathematics)
Using the idea of modified ϱ-proximal admissible mappings, we derive some new best proximity point results for ϱ−ϑ-contraction mappings in metric spaces. We also provide some illustrations to back up our work. As a result of our findings, several fixed-point results for such mappings are also found. We obtain the existence of a solution for nonlinear integral equations as an application.